PHBV/PLGA nanoparticles for enhanced delivery of 5-fluorouracil as promising treatment of colon cancer. (7th February 2020) - Handali, Somayeh; Moghimipour, Eskandar; Rezaei, Mohsen; Ramezani, Zahra; Dorkoosh, Farid Abedin
Abstract: 5-Fluorouracil (5-FU) is one of the most widely used agents in the first-line chemotherapy for colon cancer. However, clinical use of 5-FU is limited because of the low efficacy of drug uptake and systemic toxic effects. Therefore, there is a critical need to find better drug delivery systems in order to improve the efficacy of the drug. In the present study, we have developed a novel combination drug delivery system based on PHBV/PLGA NPs for delivery of 5-FU to cancer cells. NPs were prepared by the double emulsion method and their optimization of preparation was evaluated using Box–Behnken design (BBD) of response surface methodology (RSM). 5-FU loaded NPs were characterized by scanning electron microscope (SEM), differential scanning calorimetry (DSC), thermogravimetry analysis (TGA), and Fourier transformed infra-red spectroscopy (FT-IR). SEM image implied that NPs were spherical in shape and the results of DSC, TGA, and FT-IR suggest that 5-FU was encapsulated into NPs. The obtained results revealed that 5-FU loaded PHBV/PLGA NPs induced significant higher cell death at concentration much lower than free 5-FU. Results of hemolysis assay indicated that the NPs were hemo-compatible . In vivo anti-tumor studies showed that 5-FU loaded NPs reduced tumor volume significantly in comparison with free 5-FU. As the first example of using PHBV/PLGA as nano-drug delivery system with enhanced anti-tumor activities, this study establishes PHBV/PLGA as a novel promising drug delivery platform for treatment of colon cancer.